The dampening effect of employees’ future orientation on cyberloafing behaviors: the mediating role of self-control - Zhang, Heyun; Zhao, Huanhuan; Liu, Jingxuan; Xu, Yan; Lu, Hui (Frontiers in Psychology, 2015)
Previous studies on reducing employees’ cyberloafing behaviors have primarily examined the external control factors but seldomly taken individual internal subjective factors into consideration. Future orientation, an important individual factor, is defined as the extent to which one plans for future time and considers future consequences of one’s current behavior. To explore further whether and how employees’ future orientation can dampen their cyberloafing behaviors, two studies were conducted to examine the relationship between employees’ future orientation and cyberloafing behaviors. The mediation effect of employees’ objective and subjective self-control between them was also examined. In Study 1, a set of questionnaires was completed, and the results revealed that the relationship between employees’ future orientation and cyberloafing behaviors was negative, and objective self-control mediated the relationship. Next, we conducted a priming experiment (Study 2) to examine the causal relationship and psychological mechanism between employees’ future orientation and cyberloafing behaviors. The results demonstrated that employees’ future-orientation dampened their attitudes and intentions to engage in cyberloafing, and subjective self-control mediated this dampening effect. Theoretical and practical implications of these findings are also discussed.